Sensibilidad al contraste en pacientes con glaucoma primario de ángulo abierto (2022)
Contrast sensitivity is the ability to discriminate differences in luminance at various spatial frequencies. Glaucoma is an optic neuropathy and can decrease contrast sensitivity due to loss of ganglion cells and nerve fibers. Objective: To identify the contrast sensitivity values in patients with primary open-angle glaucoma and control patients, with the Pelli Robson and CSV-1000 tests. Methods: Studies published between 2006 to 2022, PubMed and Scielo were identified. Results: 6 articles in English language were analyzed, 4 descriptive observational and 2 analytical observational, evaluating patients with primary open angle glaucoma, 1 medium and moderate stage, 2 advanced and 3 without stage. Three of the studies measured contrast sensitivity with the Pelli Robson test and three with the CSV-1000. Reporting an average contrast sensitivity of 1.6 log in glaucoma patients evaluated with Pelli Robson and an average of 1.07 in low, medium and high spatial frequencies in the group of glaucoma patients measured with CSV1000E. Conclusion: The included studies evidenced the decrease in contrast sensitivity in patients with glaucoma in the CSV-1000 and Pelli Robson tests.